The Authority of The Integrated Assessment Team For Legal Certainty Regarding Rehabilitation For Suspected Drug Abusers - Muchamad Bratadewa Yuda Pratama; Erikson Sihotang; I Nyoman Suandika (Return : Study of Management, Economic and Bussines, 2024)
This study aims to analyze the authority of the Integrated Assessment Team (TAT) in determining rehabilitation for narcotics abuse victims and to identify obstacles in implementing rehabilitation recommendations, especially for those undergoing legal proceedings. The research uses a normative legal method, supported by empirical data, relying on primary legal materials such as laws and regulations, and secondary materials like literature related to the authority of TAT. The findings show that the TAT holds a crucial role in recommending medical and social rehabilitation for narcotics abusers. However, several obstacles hinder the effective implementation of TAT's recommendations, including poor coordination among law enforcement agencies and the limited resources available to support the rehabilitation process. Additionally, the social stigma surrounding narcotics abuse further complicates the rehabilitation process. The discussion emphasizes the need for stronger inter-agency coordination and increased support for rehabilitation programs to ensure better outcomes for narcotics abuse victims. The study concludes that despite the TAT’s authority being clearly regulated, several implementation challenges remain, which require urgent attention to improve the effectiveness of rehabilitation for narcotics abusers within the legal system.